OPTIMISATION OF SOLID STATE FERMENTATION OF BANANA PEELS FOR CITRIC ACID PRODUCTION (Nigerian Journal of Technology, 2015)
In this study, design of experiment (DOE) for response surface methodology (RSM) was used to analyse and optimise the simultaneous effect of solid substrate loading, initial pH and inoculum density on citric acid production from banana peels via solid state fermentation using Aspergillus niger. A three-variable, three-level Box-Behnken design was used to develop a statistical model to describe the relationship between citric acid concentration and the chosen independent variables and to optimise the production of citric acid using RSM. The model was statistically significant (p